2020
DOI: 10.1177/0004867420967747
|View full text |Cite
|
Sign up to set email alerts
|

The National Disability Insurance Scheme and people with severe and persistent mental illness/psychosocial disability: A review, analysis and synthesis of published literature

Abstract: Objectives: The aim of this scoping review was to map and synthesise peer-reviewed literature reporting on the Australian National Disability Insurance Scheme and psychosocial disability. Method: The review followed the rigorous and systematic protocol of Arksey and O’Malley. Five databases were searched and, using strict inclusion and exclusion criteria, publications were identified for inclusion. Data were extracted from publications, tabulated and graphically presented. A qualitative analysis was also compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 34 publications
2
29
0
Order By: Relevance
“…Despite Australia's significant investment in the National Disability Insurance Scheme (NDIS), which aims to increase the supports provided to people with disability to ensure that their needs are met (Cortese et al., 2020), our findings demonstrate that many young carers continue to provide significant levels of support, with consequences for their health and educational outcomes. This finding is congruent with findings of research with other family carers engaging with the NDIS who have reported a moderate increase in supports but greater challenges in accessing and coordinating assistance (Hamilton et al, 2020).…”
Section: Discussionsupporting
confidence: 87%
“…Despite Australia's significant investment in the National Disability Insurance Scheme (NDIS), which aims to increase the supports provided to people with disability to ensure that their needs are met (Cortese et al., 2020), our findings demonstrate that many young carers continue to provide significant levels of support, with consequences for their health and educational outcomes. This finding is congruent with findings of research with other family carers engaging with the NDIS who have reported a moderate increase in supports but greater challenges in accessing and coordinating assistance (Hamilton et al, 2020).…”
Section: Discussionsupporting
confidence: 87%
“…However, there has been significant, cogent discourse in the mental health community about the appropriateness of the NDIS for Australians living with mental illness. Most notably, it was found that there has been further fragmentation of the support systems experienced by people with SPMI [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…The reallocation of resources to the NDIS has reduced funding in the community mental health systems around the country to varying degrees [ 34 ]. Secondary losses include loss of qualified staff and rural and remote programs, a casualised workforce, and hybrid providers that provide NDIS and fund other mental health supports, resulting in streamlining and loss of supports offered [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data suggest that NDIS applications for a small group of people with YOD are being rejected based on a lack of knowledge among assessors or because impairments are deemed insufficiently severe to meet the criteria for disability. Difficulty meeting the NDIS eligibility requirements has been documented by other groups including those with mild intellectual disability and psychosocial disability (Hamilton et al, 2020; O’Connor, 2014).…”
Section: Discussionmentioning
confidence: 99%